Clinicopathological characteristics of breast sebaceous adenocarcinoma - Heng, Chen; Wei, Tan; Yingbing, Tu; Hanzhong, Liu (Polish Journal of Pathology, 2018)
Two middle-aged females presented with a mass located in the lateral quadrant of the breast. Both patients received modified radical surgery for breast cancer, radiotherapy, and chemotherapy and have been living without evidence of disease for more than one year. Under the microscope, we observed that the tumour cells were organised in a solid nest-like or leafy distribution and comprised sebaceous gland cells and oval or fusiform cells. The differences between the two cases are as follows: First, the mass in the first case had a mixed echo pattern on ultrasound, whereas that in the second case had a hypoechoic pattern. Pathology revealed the presence of irregular cysts in the first case, which was consistent with the ultrasound features, and microscopy revealed the presence of necrosis in the tumour. Second, the first case was strongly positive for HER-2 expression, but the second case was negative. In contrast, the second case was positive for ER expression, whereas the first case was negative. Third, the second patient had two axillary lymph node metastases, whereas the first patient had none. We analysed the obtained data to derive the following conclusions: breast sebaceous carcinoma typically occurs in middle-aged women. Under the microscope, two types of cells can be observed in a solid nest-like or leafy distribution. One cell population consists of sebaceous gland-like tumour cells, which are mostly located in the centre of the lobules or cell nests. These represent a more differentiated cell type and are rich in vacuolar cytoplasm. The other cell population consists of smaller oval or fusiform non-vacuolar cells, mostly located at the periphery of the lobules or cell nests. These cells are usually undifferentiated and are thus difficult to distinguish from typical ductal carcinoma cells. Breast sebaceous carcinoma has a high rate of positive expression of ER, PR, p53, and EMA and a low rate of positive expression of HER-2 and GCDFP-15. Primary breast sebaceous cancer has the following diagnostic characteristics: sebaceous differentiation in at least 50% of cells in the absence of any evidence of originating in the cutaneous adnexa; features, such as ductal carcinoma differentiation, lobular carcinoma differentiation, and others, which can be found in primary breast sebaceous cancer, distinct from those in skin sebaceous adenocarcinoma; and a typical transitional structure between the cancer tissue and ductal epithelium. Breast sebaceous carcinoma should be distinguished from skin sebaceous adenocarcinoma, lipid-rich carcinoma, apocrine carcinoma, and glycogen-rich clear cell carcinoma, among others. Furthermore, this is a hormone receptor-dependent type of breast cancer that requires comprehensive treatment. Thus, after extensive analysis, we conclude that breast sebaceous carcinoma has low invasiveness and good prognosis.